PENGARUH BRAND TRUS TERHADAP LOYALITAS PELANGGAN, DIMEDIASI OLEH KEPUTUSAN PEMBELIAN - Sudarwati Sudarwati; Ibnu Suryo; Ryan Susanto (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to see and analyze the effect of Brand Trust on Customer Loyalty and to measure the role of Purchase Decision as a mediating variable for the influence of Brand Trust on Customer Loyalty in MS Glow products. This research was applied to consumers of MS Glow cosmetic products in the Solo Raya area, the sample taken was 100 respondents, with sampling using a purposive sampling technique. This study was analyzed using Partial Least Square (PLS) with SmartPLS3 software. The results of the study show that Brand Trust has a positive and significant effect on Customer Loyalty. Purchase decisions have a positive and significant effect on customer loyalty. Brand Trust has a positive and significant effect on Purchasing Decisions. Brand Trust through the mediation of Purchase Decision has a positive and significant effect on Customer Loyalty. Keywords: Brand Trust, Customer Loyalty, Purchase Decision